Mycorrhizal Influence on Vegetable Crops: Enhancing Productivity and Sustainability - Upadhayay, Viabhav Kumar; Gaurav, Kumar; Yadav, Rajeev Kumar; Singh, Ashish Kumar; Kanth, Katyayni; Gangola, Saurabh; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Naik, Yogesh Dashrath (Springer Nature, 2025)
Climate change presents a significant global challenge to agricultural productivity, including in vegetable crop cultivation. Traditional chemical-based methods for enhancing vegetable quality and yield often lack sustainability and adversely affect the environment. In contrast, the use of microorganisms, such as mycorrhizal fungi, provides an eco-friendlier approach. Mycorrhizal fungi are renowned for their ability to enhance plant growth and development, especially in vegetables, by improving nutrient uptake and resilience to stress. These fungi exhibit remarkable adaptability to various soil and climatic conditions, effectively mitigating abiotic stress, enhancing nutrient availability, and suppressing plant diseases. This chapter highlights the functional benefits of mycorrhizal fungi in boosting vegetable crop productivity and quality, positioning them as a sustainable alternative to chemical agrochemicals, thereby promoting greener and more resilient agricultural practices.